Formulation and Characterization of Eplerenone Nanocrystal as Sublingual Fast-dissolving Film - Kareem, Hawraa; Rajab, Nawal (Iraqi Journal of Pharmaceutical Sciences, 2024)
Eplerenone, a Class-II according to the biopharmaceutical classification system (BCS), with poor water solubility, resulting in low bioavailability. To address these limitations, this study aimed to improve the drug solubility and dissolution rate, by formulating it as nanocrystals (NCs). The NCs were intended to enhance Eplerenone’s solubility, thereby increasing its bioavailability when taken orally. Additionally, load it as a sublingual fast-dissolving film to be released immediately and enhance effectiveness by avoiding first-pass metabolism. Using the solvent anti-solvent precipitation method, nanocrystals (NCs) of Eplerenone were prepared, and the impact of different factors on their particle size (PS) and polydispersity index (PDI) was investigated. The majority of the NCs formulations exhibited nanoscale particle sizes. Notably, the optimized formulation, F8(with 0.05% soluplus), showed a lower particle size (94.15nm), a high dissolution velocity (96.75%), and no drug-excipient interactions. Subsequently, an oral thin film containing PVA polymer and the optimized EPL nanocrystals was developed. The study results suggested that the immediate release of EPL nanocrystals from the sublingual film led to enhanced therapeutic action, improved efficacy, and increased bioavailability, as it bypassed first-pass metabolism by hepatic enzymes. Overall, nanocrystal-based sublingual films hold promise for enhancing the effectiveness of Eplerenone.